2019
DOI: 10.3390/microorganisms7120649
|View full text |Cite
|
Sign up to set email alerts
|

Blastocystis Colonization Is Associated with Increased Diversity and Altered Gut Bacterial Communities in Healthy Malian Children

Abstract: Blastocystis is the most common protozoan colonizing the gut of vertebrates. It modulates the human digestive microbiota in the absence of inflammation and gastrointestinal disease. Although it has been associated with human diseases, including inflammatory bowel disease, its pathogenicity remains controversial. This study aimed to assess the influence of Blastocystis on the gut bacterial communities in healthy children. We conducted a cross-sectional study on 147 Blastocystis-colonized and 149 Blastocystis-no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 45 publications
(55 reference statements)
5
55
0
Order By: Relevance
“…The phyla Firmicutes , Elusimicrobia , Lentisphaerae , Euryarchaeota and the species of Faecalibacterium prausnitzii (family Ruminococcaceae ) and Roseburia sp. (family Lachnospiraceae ) were associated with Blastocystis colonisation [ 80 ]. In terms of Entamoeba spp., a prospective cohort study of clinical enteric infections used qPCR detection to reveal a significantly higher level of Prevotella.…”
Section: Resultsmentioning
confidence: 99%
“…The phyla Firmicutes , Elusimicrobia , Lentisphaerae , Euryarchaeota and the species of Faecalibacterium prausnitzii (family Ruminococcaceae ) and Roseburia sp. (family Lachnospiraceae ) were associated with Blastocystis colonisation [ 80 ]. In terms of Entamoeba spp., a prospective cohort study of clinical enteric infections used qPCR detection to reveal a significantly higher level of Prevotella.…”
Section: Resultsmentioning
confidence: 99%
“…In this aim, only data obtained by molecular methods were recorded as non-molecular methods such as microscopic observation of fresh feces are known to greatly underestimate the prevalence of the parasite [ 39 , 41 ]. The prevalence of the parasite ranges between 25.6% and 100% depending on the geographical area [ 12 , 13 , 31 , 36 , 37 , 38 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. By focusing on the neighboring countries of Senegal (West Africa), the prevalence of Blastocystis sp.…”
Section: Discussionmentioning
confidence: 99%
“…By focusing on the neighboring countries of Senegal (West Africa), the prevalence of Blastocystis sp. was, respectively, 58.2% [ 38 ] and 70% [ 45 ] in two different surveys performed in Côte d’Ivoire and 49.7% in Mali [ 46 ]. Two other field studies showed a prevalence of 49% [ 31 ] and 84% [ 37 ] in Nigeria, while only one small-scale cohort screened in Liberia [ 31 ] indicated a frequency of the parasite of ~70%.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other studies have shown that the presence of Blastocystis in gut microbiota increases the abundance of some groups of beneficial bacteria (e.g., Ruminococcaceae, Lachnospiraceae, Clostridiaceae, etc.) [10][11][12].…”
Section: Introductionmentioning
confidence: 99%